Reviews (Modern theology, 1996)
Book reviewed in this article: Violence Unveiled: Humanity at the Crossroads by Gil Bailie The Feminist Question: Feminist Theology in the Light of Christian Tradition by Francis Martin Doctrine: Systematic theology, Volume II by James Wm. McClendon, Jr. Pattern of Redemption: The Theology of Hans Urs von Balthasar by Edward T. Oakes Reclaiming Dietrich Bonhowffer: The Promise of His Theology by Charles Marsh WITTGENSTEIN: A Religious Point of View? by Norman Malcolm, edited with a response by Peter Winch. God and the Philosophers: The Reconciliation of Faith and Reason, Ed. Thomas V. Morris Reasoning and Rhetoric in Religion by Nancey C. Murphy A Radical Jew: Paul and the Politics of Identity by Daniel Boyarin